The meaning in group volunteering and its influence on the well-being of community-dwelling older volunteers in Japan: A qualitative study - Kaori Hotta; Mina Ishimaru (Archives of Gerontology and Geriatrics Plus)
Background: The aging population is projected to increase globally. Creating a system where the older population can play an active role in their communities and help each other is challenging. This qualitative study aimed to determine the meaning in volunteering activities and its influence on well-being as well as the relationship between them identified by community-based older volunteers through group volunteering activities. Methods: This descriptive qualitative study followed the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. We conducted semi-structured face-to-face interviews of older adults aged >65 years (N = 12), who volunteered and routinely interacted with each other in their area of residence between February and March 2021. Results: Relationships between the meaning of volunteering and well-being were identified by community-dwelling older volunteers. Volunteering was a part of their lives and they had acquired a role in the community, which influenced their self-care for health maintenance and positive enjoyment. A place to continuously learn from each other influenced positive enjoyment, self-acceptance, self-growth, and motivation to undertake new challenges. Forming a volunteer community where supporters and recipients helped each other and had positive relationships and identifying a place for oneself also had a positive impact and stimulated interactions that sparked motivation and joy. Conclusions: The meaning in volunteering activities identified by older volunteers in the community had an impact on their well-being, including subjective and psychological well-being. A new finding of this study is the identification of these meanings, their impact on well-being, and the relationship between these meanings and well-being.